Innate Immune Responses of Calves during Transient Infection with a Noncytopathic Strain of Bovine Viral Diarrhea Virus - Müller-Doblies, Doris (American Society for Microbiology, 2004)
In this study, six immunocompetent calves were experimentally infected with a noncytopathic strain of bovine viral diarrhea virus (BVDV), and the effects of the viral infection on parameters of the innate immune response of the host were analyzed. Clinical and virological data were compared with the temporal activation of the alpha/beta interferon-regulated Mx gene in white blood cells (WBC) and skin as well as the upregulation of the acute-phase serum proteins haptoglobin (Hp) and serum amyloid A (SAA). The viral strain used did provoke transient health impairment, namely, fever and leukopenia that were associated with viremia, viral shedding with nasal secretions, and antiviral seroconversion. Complete recovery was observed within 3 weeks. Elevated levels of SAA and Hp were apparent from days 4 to 13 and 8 to 11, respectively. In WBC, the levels of Mx mRNA and Mx protein were elevated from days 2 to 15. In the context of this study with BVDV, the level of Mx protein expression in WBC provided the most telling diagnostic window to monitor the host's ongoing innate immune response.